A One‐Pot Copper‐Catalyzed 3‐Fold C–N Bond Coupling Strategy to the Synthesis of Substituted Benzimidazoles. Issue 44 (5th June 2020) - Subramanian, Parthasarathi; Kaliappan, Krishna P.
Abstract : An efficient, one‐pot copper catalyzed 3‐fold C–N bond‐coupling strategy leading to pharmaceutically relevant benzimidazole heterocycles is reported. Our strategy involves a copper catalyzed intramolecular C–N coupling of N, N' ‐bis(2‐bromophenyl)formamidine to provide 1‐(2‐bromophenyl)‐1H‐benzimidazole which upon intermolecular coupling with 2‐amino pyridines and a cascade sp 2 C–H amination furnished a range of benzimidazo[1, 2‐ a ]benzimidazoles. Abstract : One‐pot reaction leading to direct access to biologically relevant heterocycles is highly recommended in chemical synthesis. One such standout method, manifold C–N bond formations route to the synthesis of benzimidazo[1, 2‐ a ]benzimidazoles, is described. Our methodology involves a copper catalyzed intramolecular C–N coupling of N, N' ‐bis(2‐bromophenyl)formimidamide to provide 1‐(2‐bromophenyl)‐1H‐benzimidazole which upon intermolecular coupling with 2‐amino pyridines and a cascade sp 2 C–H amination provided a range of benzimidazo[1, 2‐ a ]benzimidazoles.